2006
DOI: 10.1182/blood-2005-01-015081
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of systemic and local neutrophil responses by G-CSF during pulmonary Pseudomonas aeruginosa infection

Abstract: Granulocyte colony-stimulating factor (G-CSF) regulates the production, maturation, and function of neutrophils. Its expression is often induced during infection, resulting in high concentrations of G-CSF in inflammatory exudates and in the blood, suggesting that it may regulate both local and systemic neutrophil responses. Herein, we characterize the neutrophil response in G-CSFR−/− mice following intratracheal injection with Pseudomonas aeruginosa–laden agarose beads, modeling the pulmonary infection observe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
51
0
3

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 72 publications
(58 citation statements)
references
References 59 publications
3
51
0
3
Order By: Relevance
“…5). Consistent with previous studies (22,38), under basal conditions, 1.84% ± 0.32% of WT neutrophils were present in the blood ( Figure 1D). In contrast, the percentage of Cxcr2 -/-neutrophils in the blood was 0.57% ± 0.18% (P = 0.02).…”
Section: Resultssupporting
confidence: 91%
“…5). Consistent with previous studies (22,38), under basal conditions, 1.84% ± 0.32% of WT neutrophils were present in the blood ( Figure 1D). In contrast, the percentage of Cxcr2 -/-neutrophils in the blood was 0.57% ± 0.18% (P = 0.02).…”
Section: Resultssupporting
confidence: 91%
“…Gregory et al 49 reported that apoptosis of neutrophils was accelerated in the Pseudomonas aeruginosa-infected lungs in G-CSFR Ϫ/Ϫ mice. Therefore, the production of G-CSF in the tumor microenvironment may promote the maintenance of tumor infiltrating neutrophils, in addition to accelerating the neutrophil production in the BM.…”
Section: Discussionmentioning
confidence: 99%
“…G-CSF regulates the production and maturation of neutrophils. It also stimulates the survival of mature neutrophils (Gregory et al, 2007). These proinflammatory activities of IL-1␤, IL-6, and G-CSF may contribute to abscess formation.…”
mentioning
confidence: 99%